Dietary patterns, genetic predisposition, and risk of cholelithiasis: a large-scale prospective cohort study - Jin, Kecheng; Mi, Ningning; He, Wangping; Zhong, Ruyang; Jin, Boru; Liu, Zhen; Dong, Chunlu; Lin, Yanyan; Yue, Ping; Xia, Bin; He, Qiangsheng; Yuan, Jinqiu; et al. (Frontiers in Nutrition, 2024)
Background: Limited epidemiological evidence exists concerning the impact of healthy dietary patterns on reducing the risk of cholelithiasis. We aimed to examine the association of seven established dietary patterns with subsequent cholelithiasis risk and whether this association was modified by genetic risk.We conducted a prospective cohort study from the UK Biobank, including 155,323 participants initially free of cholelithiasis and cholecystectomy. Dietary patterns were assessed using a validated food frequency questionnaire (Oxford WebQ), covering Mediterranean Diet Score (MED), alternate Mediterranean Diet Score(aMED), overall Plant-based Diet Index (PDI), healthy Plant-based Diet Index (hPDI), unhealthy Plant-based Diet Index (uPDI), Healthy Eating Index 2015 (HEI-2015) and EAT-lancet Score. Genetic risk was quantified and stratified by a polygenic risk score (PRS) incorporating 13 known cholelithiasis-associated loci. Cox proportional hazards regression was employed to estimate the association between dietary patterns, PRS, and cholelithiasis incidence, adjusting for potential confounders.Results: During a median follow-up of 13.3 years, 5056 cases of cholelithiasis were identified. After adjusting for potential confounders, adherence to aMED and HEI-2015 dietary patterns reduced cholelithiasis risk by 10% (HR:0.90; 95%CI: 0.83-0.98) and 11% (HR:0.89; 95%CI:0.82-0.96), respectively. A significant decrease in cholelithiasis risk was observed across PRS quintiles, low PRS was associated with a 16% reduced risk (HR:0.84; 95%CI:0.77-0.92). Participants with both high dietary scores and low genetic risk had the lowest cholelithiasis risk, with an HR of 0.76 (95%CI: 0.64-0.91) for aMED and 0.73 (95%CI: 0.61-0.88) for HEI-2015.Higher adherence to aMED and HEI-2015 might significantly decrease the risk of cholelithiasis, irrespective of genetic risk. Our results highlighted the potential of diet intervention for cholelithiasis prevention in the general population.